朝向容納多元性別教育： 中學教師推動同志教育之經驗探析 - 蔣琬斯 Wan-Ssu Chiang,; 游美惠 Mei-Hui You (Journal of Curriculum Studies, 2022)
同志教育是目前「性別平等教育」課程中受到最多質疑與阻抗的一部分。本研究採質性研究方式訪談19位中學教師，探討他們在校園中落實同志教育之經驗與行動策略。研究發現：這些教師均是從察覺到同志學生的出櫃擔憂開始投入同志教育的推動，而後透過研習與進修進一步察覺到自己過往所持有之偏見，並深刻反思到社會上對於同志與異性戀者的雙重標準，更積極將同志教育從課堂教室拓展到整個校園。另外值得注意的是，有些教師以不刻意談同志的方式來推動同志教育，反而帶來教學效果。本研究最後提出建議將「同志教育」一詞更名為「容納多元性別教育」，以涵蓋性別的多元樣貌。 “Gay and lesbian education,” as officially translated by the Ministry of Education, has been a part of the curriculum mandated by Taiwan’s Gender Equity Education Act since 2004; yet, the implementation of the standard has faced strong resistance over the years. This research used qualitative methods to examine the pedagogic strategies and classroom experiences of nineteen secondary school educators with experience implementing gay and lesbian education. All of the interviewed educators began incorporating gay and lesbian education in the classroom after observing students struggle with coming out. As they advanced their understanding through professional development, they were able to realize their own past prejudices and reflect on existing double standards in the treatment of LGBT+ individuals. After learning how to implement gay and lesbian education in their own classrooms, these educators were eventually able to expand their influence to other areas of campus. Notably, effective strategies did not always require deliberate discussions of sexuality or gender. Ultimately, this study concludes the official term “gay and lesbian education” is far too narrow in scope and, instead, recommends the standard be renamed as “LGBT+ inclusive education” to more broadly reflect the diverse dimensions of gender.